Cognitive Function in Acquired Bilateral Vestibulopathy: A Cross-Sectional Study on Cognition, Hearing, and Vestibular Loss - Dobbels, Bieke; Mertens, Griet; Gilles, Annick; Claes, Annes; Moyaert, Julie; van de Berg, Raymond; Van de Heyning, Paul; Vanderveken, Olivier; Van Rompaey, Vincent (Frontiers in Neuroscience, 2019)
BACKGROUND: Several studies have demonstrated cognitive deficits in patients with bilateral vestibulopathy (BVP). So far, little attention has been paid to the hearing status of vestibular patients when evaluating their cognition. Given the well-established link between sensorineural hearing loss (SNHL) and cognitive decline and the high prevalence of SNHL in BVP patients, it is therefore uncertain if the cognitive deficits in BVP patients are solely due to their vestibular loss or might be, partially, explained by a concomitant SNHL. OBJECTIVE. To evaluate the link between cognition, hearing and vestibular loss in BVP patients DESIGN: Prospective cross-sectional analysis of cognitive performance in patients with BVP and control participants without vestibular loss. Both groups included subjects with a variety of hearing (dys)function. Cognition was assessed by means of the Repeatable Battery for the Assessment of Neuropsychological Status for Hearing Impaired Individuals (RBANS-H). RESULTS. Sixty-four BVP patients were evaluated and compared with 83 control participants. For each subscale and the totale RBANS-H scale a multiple linear regression model was fitted with the following variables: vestibular loss, hearing loss, age, gender and education. Hearing loss seemed to be associated with worse outcome on the total RBANS-H scale and subscales immediate memory and language. Vestibular loss, on the other hand, was linked to worse performance on the attention subscale of the RBANS-H. Furthermore, we did not observe a correlation between saccular function and cognition. CONCLUSION. This study has found general cognitive deficits in a large sample size of BVP patients. Multiple linear regression models revealed that both vestibular and hearing dysfunction were associated with different subscales of the cognitive test battery, the RBANS-H. Whereas hearing loss was associated with worse performance on total RBANS-H score, immediate memory and language, vestibular loss was observed to negatively affect attention performance.